Mildew-proof and antibacterial polyolefin material and its processing technology and application

CN120484379BActive Publication Date: 2026-10-27YANGZHOU RUERMEI DAILY NECESSITIES CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510748428.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-06
Publication Date
2026-10-27
Estimated Expiration
2045-06-06

AI Technical Summary

Technical Problem

然而,聚烯烃材料在潮湿阴暗环境下容易滋生细菌和霉菌,尤其是在医院、食品加工、卫生洁具等对卫生要求较高的领域,其使用会带来交叉感染等卫生问题

Benefits of technology

1、本发明的一种防霉抗菌聚烯烃材料及其加工工艺和应用,壳聚糖具有优异抗菌性能如生物可降解性、广谱抑菌性、生物兼容性等,利用1-(3-二甲胺基丙基)-3-乙基碳二亚胺(EDC)/N-羟基琥珀酰亚胺(NHS)化学交联法将山梨酸接枝到壳聚糖上形成壳聚糖-山梨酸接枝共聚物,引入不饱和双键;最后,然后在壳聚糖的C6位羟基上接枝2,3-环氧丙基三甲基氯化铵(GTA)季铵盐,得到改性壳聚糖,进一步提升材料的抗菌性和生物相容性,延长材料的使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of polyolefin materials, in particular to a mildew-proof and antibacterial polyolefin material, a processing technology thereof and application thereof.The mildew-proof and antibacterial polyolefin material comprises the following components by weight: polypropylene 60-80 parts, elastomer 5-15 parts, maleic anhydride grafted polypropylene 2-5 parts, white oil 15-25 parts, talcum powder 10-30 parts, mildew-proof and antibacterial agent 1-5 parts, antioxidant 0.5-1.0 parts, lubricant 1-3 parts.The mildew-proof and antibacterial agent is a mixture of 0.5-2.0 parts of modified nano zinc oxide, 0.3-1.5 parts of methylisothiazolinone and 0.2-1.5 parts of epsilon-polylysine hydrochloride.The mildew-proof and antibacterial polyolefin material prepared by the present application has excellent mechanical properties and mildew-proof and antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyolefin materials technology, specifically to an anti-mildew and antibacterial polyolefin material, its processing technology, and its application. Background Technology

[0002] With the improvement of people's living standards and the enhancement of health awareness, the requirements for living environment and product quality are also getting higher and higher, and the demand for polyolefin materials with anti-mildew and antibacterial functions is growing. Especially in fields with strict hygiene requirements such as medical, food, and sanitation, as well as in environments that are easily contaminated by microorganisms, such as damp bathrooms and kitchens, anti-mildew and antibacterial polyolefin materials have broad application prospects.

[0003] Polyolefin materials, such as polyethylene and polypropylene, are widely used in the manufacture of pipes, daily necessities, films, appliance casings, and automotive interiors due to their low production cost, good overall mechanical properties, non-toxicity, light weight, corrosion resistance, and ease of processing and recycling. However, polyolefin materials are prone to bacterial and mold growth in humid and dark environments, especially in areas with high hygiene requirements such as hospitals, food processing, and sanitary ware manufacturing, where their use can lead to cross-infection and other hygiene problems. Many existing antibacterial agents are prone to degradation during use, particularly in high-temperature and high-humidity environments, where their antibacterial effect is significantly reduced, preventing materials from maintaining their antibacterial properties for extended periods.

[0004] Therefore, we propose a mildew-resistant and antibacterial polyolefin material, its processing technology, and its application. Summary of the Invention

[0005] The purpose of this invention is to provide a mildew-resistant and antibacterial polyolefin material, its processing technology, and its application, in order to solve the problems raised in the prior art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A processing technology for an anti-mildew and antibacterial polyolefin material includes the following steps: After mixing polypropylene, elastomer and white oil evenly, maleic anhydride-grafted polypropylene, talc, antifungal and antibacterial agent, antioxidant and lubricant are added and mixed evenly. The mixture is then melt-extruded and granulated using a twin-screw extruder at an extrusion temperature of 180-220℃ to obtain an antifungal and antibacterial polyolefin material.

[0007] Furthermore, the anti-mildew and antibacterial polyolefin material comprises the following components by weight: 60-80 parts of polypropylene, 5-15 parts of elastomer, 2-5 parts of maleic anhydride-grafted polypropylene, 15-25 parts of white oil, 10-30 parts of talc, 1-5 parts of anti-mildew and antibacterial agent, 0.5-1.0 parts of antioxidant, and 1-3 parts of lubricant.

[0008] Furthermore, the elastomer is one or more of ethylene-hexene copolymer, ethylene-butene copolymer, and ethylene-octene copolymer.

[0009] Furthermore, the antifungal and antibacterial agent is a mixture of 0.5-2.0 parts modified nano zinc oxide, 0.3-1.5 parts methylisothiazolinone and 0.2-1.5 parts ε-polylysine hydrochloride.

[0010] Furthermore, the preparation method of the modified nano zinc oxide is as follows: Step 1: Add nano zinc oxide to a mixed solution of anhydrous ethanol and deionized water, sonicate for 10-30 min, add vinyltriethoxysilane and mix, adjust the pH of the system to 4-5, react at 60-70℃ for 4-6 h, centrifuge, wash and dry to obtain vinyl nano zinc oxide. Step 2: Dissolve polyhexamethylene guanidine hydrochloride in dimethyl sulfoxide, add 4-epoxyisoeugenol, react at 50-60℃ for 22-24 h, filter, wash and dry to obtain a compound containing a double bond guanidine group; Step 3: Mix vinyl nano zinc oxide and deionized water evenly, add methyl methacrylate, a compound containing a double bond guanidine group and modified chitosan, purge with nitrogen gas, add potassium persulfate, and react at 70-80℃ for 10-12 hours. After centrifugation, washing and drying, modified nano zinc oxide is obtained.

[0011] Furthermore, in step one, the mass ratio of nano zinc oxide, anhydrous ethanol, deionized water and vinyltrimethoxysilane is 1:(15-20):(3-5):(1-3).

[0012] Furthermore, in step two, the molar ratio of polyhexamethylene guanidine hydrochloride to 4-epoxyisoeugenol is 1:1.

[0013] Furthermore, in step three, the mass ratio of vinyl nano zinc oxide, deionized water, methyl methacrylate, guanidine compound containing double bonds, and modified chitosan is 1:(15-20):(1-2):(2-4):(0.5-1.5).

[0014] Furthermore, the amount of potassium persulfate used is 1-3% of the total mass of vinyl nano zinc oxide, methyl methacrylate, double-bonded guanidine compound, and modified chitosan.

[0015] Furthermore, the preparation method of the modified chitosan is as follows: Sorbic acid and ethanol were mixed evenly, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, MES buffer, and N-hydroxysuccinimide were added. The mixture was reacted in an ice bath for 1-2 hours, and then chitosan solution was added. The mixture was reacted at room temperature for 10-12 hours. After dialysis and drying, chitosan-sorbic acid graft copolymer was obtained. Chitosan-sorbic acid graft copolymer and ethanol were mixed evenly, and sodium hydroxide solution was added to adjust the pH to 9-10. 2,3-epoxypropyltrimethylammonium chloride was added, and the mixture was reacted at 60-70℃ for 5-7 hours. After precipitation, filtration, washing, and drying, modified chitosan was obtained.

[0016] Further, the mass ratio of sorbic acid, ethanol, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, MES buffer and N-hydroxysuccinimide is 1:(5-10):(0.1-0.2):(1-2):(0.08-1.0), and the pH of the MES buffer is 5.5.

[0017] Furthermore, the amount of chitosan solution used is 50-75 times the mass of sorbic acid, the concentration of chitosan solution is 2-4 wt%, and the solvent is 2 wt% acetic acid solution.

[0018] Furthermore, the mass ratio of the chitosan-sorbic acid graft copolymer, ethanol, and 2,3-epoxypropyltrimethylammonium chloride is 1:(15-30):(3-5), and the concentration of the sodium hydroxide solution is 40wt%.

[0019] Furthermore, the lubricant is one or a mixture of polypropylene wax, polyethylene wax, silicone masterbatch, polytetrafluoroethylene, and paraffin powder.

[0020] Furthermore, the antioxidant is antioxidant 1010.

[0021] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention relates to an antifungal and antibacterial polyolefin material, its processing technology, and its application. Chitosan possesses excellent antibacterial properties such as biodegradability, broad-spectrum antibacterial activity, and biocompatibility. Sorbic acid is grafted onto chitosan using a 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) / N-hydroxysuccinimide (NHS) chemical crosslinking method to form a chitosan-sorbic acid graft copolymer, introducing unsaturated double bonds. Finally, 2,3-epoxypropyltrimethylammonium chloride (GTA) quaternary ammonium salt is grafted onto the C6 hydroxyl group of chitosan to obtain modified chitosan, further enhancing the antibacterial properties and biocompatibility of the material and extending its service life.

[0022] 2. The present invention relates to an antifungal and antibacterial polyolefin material, its processing technology and application, wherein a functionalized polyhexamethylene guanidine hydrochloride containing carbon-carbon double bond groups is prepared by reacting the terminal amino group in polyhexamethylene guanidine hydrochloride with the epoxy group in 4-epoxyisoeugenol. This is a compound containing a double bond guanidine group, which can be used as a macromonomer and copolymerized with other monomers to significantly improve the antibacterial long-lasting effect. Vinyl trimethoxysilane (VTES) was used to modify the surface of nano-zinc oxide to obtain vinyl nano-zinc oxide. Finally, methyl methacrylate, a guanidine compound containing double bonds, and modified chitosan were copolymerized and coated on the surface of modified chitosan via free radical copolymerization to form a high-density layer, which significantly improved the antibacterial effect. This method is beneficial for improving its compatibility and dispersibility in polypropylene matrix (PP), reducing phase separation, and solving the problem of traditional small molecule antibacterial agents being prone to migration and dissolution, resulting in short-lived antibacterial effects. In this method, the guanidine compound itself has broad-spectrum antibacterial properties and forms a synergistic effect with modified chitosan and nano-zinc oxide, enhancing the antifungal and antibacterial effects through multiple mechanisms such as contact sterilization and inhibition of microbial metabolism.

[0023] 2. The present invention relates to an antifungal and antibacterial polyolefin material, its processing technology and application, wherein an antifungal and antibacterial agent is obtained by compounding modified nano zinc oxide, methylisothiazolinone and ε-polylysine hydrochloride. The prepared polyolefin material not only has excellent antifungal and antibacterial properties, but also extends the service life of the material. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] In this embodiment, the polypropylene (PP K8303) was purchased from Yanshan Petrochemical; the elastomer was ethylene-octene copolymer (VERSIFY POE 2300, Dow Chemical); the talc (5000 mesh) was purchased from Jiangyin Guangyuan Ultrafine Powder Co., Ltd.; the maleic anhydride-grafted polypropylene (Exxelor PO 1020) was purchased from ExxonMobil; the white oil (No. 3) was purchased from Dongguan Kangjin New Material Technology Co., Ltd.; the nano zinc oxide (20nm) was purchased from Shanghai Yaotian New Material Technology Co., Ltd.; the methylisothiazolinone was used; the ε-polylysine hydrochloride (P2658) was purchased from Merck; the polyhexamethylene guanidine hydrochloride (PGHC) was purchased from Hubei Kemaidi Chemical Co., Ltd.; the lubricant was polyethylene wax (Honeywell AC-6A); and the antioxidant was antioxidant 1010.

[0026] Unless otherwise specified, all the following quantities are parts by weight.

[0027] Example 1: A processing technology for an anti-mildew and antibacterial polyolefin material, comprising the following processes: After mixing 60 parts polypropylene, 5 parts elastomer, and 15 parts white oil evenly, 2 parts maleic anhydride-grafted polypropylene, 10 parts talc, 1 part antifungal and antibacterial agent, 0.5 parts antioxidant, and 1 part lubricant are added and mixed evenly. The mixture is then melt-extruded and granulated using a twin-screw extruder at an extrusion temperature of 180℃ to obtain an antifungal and antibacterial polyolefin material. The antifungal and antibacterial agent is a mixture of 0.5 parts modified nano zinc oxide, 0.3 parts methylisothiazolinone, and 0.2 parts ε-polylysine hydrochloride. The preparation method of modified nano zinc oxide is as follows: Step 1: Add 0.5 parts of nano zinc oxide to a mixed solution of 7.5 parts of anhydrous ethanol and 1.5 parts of deionized water, sonicate for 10 min, add 0.5 parts of vinyltriethoxysilane and mix, adjust the pH of the system to 4, react at 60℃ for 4 h, centrifuge, wash and dry to obtain vinyl nano zinc oxide. Step 2: Dissolve 1 part of polyhexamethylene guanidine hydrochloride in dimethyl sulfoxide, add 4-epoxyisoeugenol, react at 50°C for 22 h, filter, wash and dry to obtain a compound containing a double bond guanidine group; the molar ratio of polyhexamethylene guanidine hydrochloride to 4-epoxyisoeugenol is 1:1; Step 3: Mix 0.5 parts of vinyl nano zinc oxide and 7.5 parts of deionized water evenly, add 0.5 parts of methyl methacrylate, 1 part of a compound containing a double bond guanidine group and 0.25 parts of modified chitosan, purge with nitrogen gas, add 0.023 parts of potassium persulfate, react at 70°C for 10 hours, centrifuge, wash and dry to obtain modified nano zinc oxide; The preparation method of modified chitosan is as follows: 0.25 parts of sorbic acid and 1.25 parts of ethanol were mixed evenly, and 0.025 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 0.25 parts of MES buffer, and 0.02 parts of N-hydroxysuccinimide were added. The mixture was reacted in an ice bath for 1 hour, and then 12.5 parts of 2wt% chitosan solution were added. The mixture was reacted at room temperature for 10 hours. After dialyzing and drying, chitosan-sorbic acid graft copolymer was obtained. 0.25 parts of chitosan-sorbic acid graft copolymer and 3.75 parts of ethanol were mixed evenly, and 40wt% sodium hydroxide solution was added to adjust the pH to 9. 0.75 parts of 2,3-epoxypropyltrimethylammonium chloride were added. The mixture was reacted at 60℃ for 5 hours. After precipitation, filtration, washing, and drying, modified chitosan was obtained.

[0028] Example 2: A processing technology for an anti-mildew and antibacterial polyolefin material, comprising the following processes: After mixing 70 parts polypropylene, 10 parts elastomer, and 20 parts white oil evenly, 4 parts maleic anhydride-grafted polypropylene, 20 parts talc, 3 parts antifungal and antibacterial agent, 0.8 parts antioxidant, and 2 parts lubricant are added and mixed evenly. The mixture is then melt-extruded and granulated using a twin-screw extruder at an extrusion temperature of 200℃ to obtain an antifungal and antibacterial polyolefin material. The antifungal and antibacterial agent is a mixture of 1 part modified nano zinc oxide, 1 part methylisothiazolinone, and 1 part ε-polylysine hydrochloride. The preparation method of modified nano zinc oxide is as follows: Step 1: Add 1 part of nano zinc oxide to a mixed solution of 18 parts of anhydrous ethanol and 4 parts of deionized water, sonicate for 20 min, add 2 parts of vinyltriethoxysilane and mix, adjust the pH of the system to 4.5, react at 65℃ for 5 h, centrifuge, wash and dry to obtain vinyl nano zinc oxide; Step 2: Dissolve 3 parts of polyhexamethylene guanidine hydrochloride in dimethyl sulfoxide, add 4-epoxyisoeugenol, react at 55°C for 23 h, filter, wash and dry to obtain a compound containing double-bonded guanidine groups; the molar ratio of polyhexamethylene guanidine hydrochloride to 4-epoxyisoeugenol is 1:1; Step 3: Mix 1 part of vinyl nano zinc oxide and 18 parts of deionized water evenly, add 1.5 parts of methyl methacrylate, 3 parts of guanidine compound containing double bond and 1 part of modified chitosan, purge with nitrogen gas, add 0.13 parts of potassium persulfate, react at 75°C for 11 hours, centrifuge, wash and dry to obtain modified nano zinc oxide; The preparation method of modified chitosan is as follows: 0.6 parts of sorbic acid and 4.8 parts of ethanol were mixed evenly, and 0.09 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 0.9 parts of MES buffer, and 0.5 parts of N-hydroxysuccinimide were added. The mixture was reacted in an ice bath for 1.5 h, and then 40 parts of 3wt% chitosan solution were added. The mixture was reacted at room temperature for 11 h. After dialyzing and drying, chitosan-sorbic acid graft copolymer was obtained. 1 part of chitosan-sorbic acid graft copolymer and 18 parts of ethanol were mixed evenly, and 40wt% sodium hydroxide solution was added to adjust the pH to 9.5. 4 parts of 2,3-epoxypropyltrimethylammonium chloride were added, and the mixture was reacted at 65℃ for 6 h. After precipitation, filtration, washing, and drying, modified chitosan was obtained.

[0029] Example 3: A processing technology for an anti-mildew and antibacterial polyolefin material, comprising the following processes: After mixing 80 parts of polypropylene, 15 parts of elastomer, and 25 parts of white oil evenly, 5 parts of maleic anhydride-grafted polypropylene, 30 parts of talc, 5 parts of antifungal and antibacterial agent, 1 part of antioxidant, and 3 parts of lubricant are added and mixed evenly. The mixture is then melt-extruded and granulated using a twin-screw extruder at an extrusion temperature of 220℃ to obtain an antifungal and antibacterial polyolefin material. The antifungal and antibacterial agent is a mixture of 2.0 parts of modified nano zinc oxide, 1.5 parts of methylisothiazolinone, and 1.5 parts of ε-polylysine hydrochloride. The preparation method of modified nano zinc oxide is as follows: Step 1: Add 2 parts of nano zinc oxide to a mixed solution of 40 parts of anhydrous ethanol and 10 parts of deionized water, sonicate for 30 min, add 6 parts of vinyltriethoxysilane and mix, adjust the pH of the system to 5, react at 70℃ for 6 h, centrifuge, wash and dry to obtain vinyl nano zinc oxide. Step 2: Dissolve 8 parts of polyhexamethylene guanidine hydrochloride in dimethyl sulfoxide, add 4-epoxyisoeugenol, react at 60°C for 24 h, filter, wash and dry to obtain a compound containing double-bonded guanidine groups; the molar ratio of polyhexamethylene guanidine hydrochloride to 4-epoxyisoeugenol is 1:1; Step 3: Mix 2 parts of vinyl nano zinc oxide and 40 parts of deionized water evenly, add 4 parts of methyl methacrylate, 8 parts of double-bonded guanidine compound and 3 parts of modified chitosan, purge with nitrogen gas, add 0.51 parts of potassium persulfate, react at 80°C for 12 hours, centrifuge, wash and dry to obtain modified nano zinc oxide; The preparation method of modified chitosan is as follows: One part of sorbic acid and 10 parts of ethanol were mixed evenly, and 0.2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 2 parts of MES buffer, and 1 part of N-hydroxysuccinimide were added. The mixture was reacted in an ice bath for 2 hours, and then 75 parts of 4wt% chitosan solution were added. The mixture was reacted at room temperature for 12 hours. After dialyzing and drying, chitosan-sorbic acid graft copolymer was obtained. Three parts of chitosan-sorbic acid graft copolymer and 90 parts of ethanol were mixed evenly, and 40wt% sodium hydroxide solution was added to adjust the pH to 10. Then 15 parts of 2,3-epoxypropyltrimethylammonium chloride were added. The mixture was reacted at 70℃ for 7 hours. After precipitation, filtration, washing, and drying, modified chitosan was obtained.

[0030] Comparative Example 1: A processing technology for an anti-mildew and antibacterial polyolefin material, comprising the following processes: Compared with Example 2, the antifungal and antibacterial agent of Comparative Example 1 was a mixture of 1 part nano zinc oxide, 1 part methylisothiazolinone and 1 part ε-polylysine hydrochloride; the modified nano zinc oxide in Comparative Example 1 was replaced with the same mass of nano zinc oxide, and the other steps were the same as in Example 2.

[0031] Comparative Example 2: A processing technology for an anti-mildew and antibacterial polyolefin material, comprising the following processes: The preparation method of modified nano zinc oxide is as follows: Step 1: Add 1 part of nano zinc oxide to a mixed solution of 18 parts of anhydrous ethanol and 4 parts of deionized water, sonicate for 20 min, add 2 parts of vinyltriethoxysilane and mix, adjust the pH of the system to 4.5, react at 65℃ for 5 h, centrifuge, wash and dry to obtain vinyl nano zinc oxide; Step 2: Dissolve 3 parts of polyhexamethylene guanidine hydrochloride in dimethyl sulfoxide, add 4-epoxyisoeugenol, react at 55°C for 23 h, filter, wash and dry to obtain a compound containing double-bonded guanidine groups; the molar ratio of polyhexamethylene guanidine hydrochloride to 4-epoxyisoeugenol is 1:1; Step 3: Mix 1 part of vinyl nano zinc oxide and 18 parts of deionized water evenly, add 1.5 parts of methyl methacrylate and 3 parts of a compound containing a double bond guanidine group, purge with nitrogen gas, add 0.13 parts of potassium persulfate, react at 75°C for 11 hours, centrifuge, wash, and dry to obtain modified nano zinc oxide; Compared with Example 2, no modified chitosan was added in step three of Comparative Example 2, while the other steps were the same as in Example 2.

[0032] Comparative Example 3: A processing technology for an anti-mildew and antibacterial polyolefin material, comprising the following processes: The preparation method of modified nano zinc oxide is as follows: Step 1: Add 1 part of nano zinc oxide to a mixed solution of 18 parts of anhydrous ethanol and 4 parts of deionized water, sonicate for 20 min, add 2 parts of vinyltriethoxysilane and mix, adjust the pH of the system to 4.5, react at 65℃ for 5 h, centrifuge, wash and dry to obtain vinyl nano zinc oxide; Step 3: Mix 1 part of vinyl nano zinc oxide and 18 parts of deionized water evenly, add 1.5 parts of methyl methacrylate and 1 part of modified chitosan, purge with nitrogen gas, add 0.13 parts of potassium persulfate, react at 75°C for 11 hours, centrifuge, wash and dry to obtain modified nano zinc oxide. The preparation method of modified chitosan is as follows: 0.6 parts of sorbic acid and 4.8 parts of ethanol were mixed evenly, and 0.09 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 0.9 parts of MES buffer, and 0.5 parts of N-hydroxysuccinimide were added. The mixture was reacted in an ice bath for 1.5 h, and then 40 parts of 3wt% chitosan solution were added. The mixture was reacted at room temperature for 11 h. After dialyzing and drying, chitosan-sorbic acid graft copolymer was obtained. 1 part of chitosan-sorbic acid graft copolymer and 18 parts of ethanol were mixed evenly, and 40wt% sodium hydroxide solution was added to adjust the pH to 9.5. 4 parts of 2,3-epoxypropyltrimethylammonium chloride were added, and the mixture was reacted at 65℃ for 6 h. After precipitation, filtration, washing, and drying, modified chitosan was obtained. Compared with Example 2, no compound containing a double-bonded guanidine group was added in step three of Comparative Example 3, while the other steps were the same as in Example 2.

[0033] Comparative Example 4: A processing technology for an anti-mildew and antibacterial polyolefin material, comprising the following processes: Compared with Example 2, the antifungal and antibacterial agent of Comparative Example 4 was a mixture of 1 part nano zinc oxide and 1 part ε-polylysine hydrochloride, and the other steps were the same as in Example 2.

[0034] Experiment: The antifungal and antibacterial polyolefin materials obtained in Examples 1-3 and Comparative Examples 1-4 were injection molded into standard samples at an injection temperature of 240℃. Their properties were tested and the results were recorded. Tensile strength test: Tested according to GB / T 1040.2-2022, test speed is 50mm / min.

[0035] Antibacterial performance test: Tested according to JIS Z2801-2012, the bacteria used for testing were Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 6538P, and the sample size was 50mm×50mm×2mm.

[0036] Anti-mold performance test: Tested according to JIS Z2911-2018. The test species included Aspergillus niger ATCC 6275, Penicillium pineophilum ATCC 36839, Penicillium wansi ATCC 18502, Trichoderma viride ATCC 9645 and Chaetomium globulus ATCC 6205. Grade 0 means no mold growth, Grade 1 means initial growth, and Grade 2 means general anti-mold performance with visible mold growth. The sample surface coverage area is 10%-30%.

[0037] The test results are shown in Table 1.

[0038] Table 1. Performance test results of anti-mildew and antibacterial polyolefin materials

[0039] Based on the data in the table above, the following conclusions can be clearly drawn: 1. Compared with Examples 1-3, the tensile strength, antibacterial rate and antifungal grade of the products obtained in Comparative Examples 1 and 4 all decreased, indicating that the present invention significantly improved the mechanical properties and antifungal and antibacterial properties of the material by preparing modified nano zinc oxide; and further improved the antifungal and antibacterial properties of the material by introducing methylisothiazolinone to be compounded with nano zinc oxide and ε-polylysine hydrochloride.

[0040] 2. Compared with Examples 1-3, the antibacterial rate and antifungal grade of the products obtained in Comparative Examples 2 and 3 decreased after 30 days. This indicates that the present invention significantly improves the anticorrosive and antibacterial properties of the material by introducing modified chitosan and compounds containing double bonds to exert a synergistic effect, and also enhances the compatibility and stability of the material, ensuring its effectiveness in long-term use.

[0041] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A processing technology for an anti-mildew and antibacterial polyolefin material, characterized in that: Includes the following steps: After polypropylene, elastomer and white oil are mixed evenly, maleic anhydride-grafted polypropylene, talc, antifungal and antibacterial agent, antioxidant and lubricant are added and mixed evenly. The mixture is then melt-extruded and granulated using a twin-screw extruder at an extrusion temperature of 180-220℃ to obtain an antifungal and antibacterial polyolefin material. The anti-mildew and antibacterial polyolefin material comprises the following components by weight: 60-80 parts polypropylene, 5-15 parts elastomer, 2-5 parts maleic anhydride-grafted polypropylene, 15-25 parts white oil, 10-30 parts talc, 1-5 parts anti-mildew and antibacterial agent, 0.5-1.0 parts antioxidant, and 1-3 parts lubricant. The antifungal and antibacterial agent is a mixture of 0.5-2.0 parts modified nano zinc oxide, 0.3-1.5 parts methylisothiazolinone and 0.2-1.5 parts ε-polylysine hydrochloride; The modified nano zinc oxide is prepared as follows: Step 1: Add nano zinc oxide to a mixed solution of anhydrous ethanol and deionized water, sonicate for 10-30 min, add vinyltriethoxysilane and mix, adjust the pH of the system to 4-5, react at 60-70℃ for 4-6 h, centrifuge, wash and dry to obtain vinyl nano zinc oxide. Step 2: Mix polyhexamethylene guanidine hydrochloride and dimethyl sulfoxide evenly, add 4-epoxyisoeugenol, react at 50-60℃ for 22-25h, filter, wash and dry to obtain a compound containing double bond guanidine groups; Step 3: Mix vinyl nano zinc oxide and deionized water evenly, add methyl methacrylate, a compound containing a double bond guanidine group and modified chitosan, purge with nitrogen gas, add potassium persulfate, react at 70-80℃ for 10-12 hours, centrifuge, wash and dry to obtain modified nano zinc oxide; The modified chitosan is prepared as follows: Sorbic acid and ethanol were mixed evenly, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, MES buffer, and N-hydroxysuccinimide were added. The mixture was reacted in an ice bath for 1-2 hours, and then chitosan solution was added. The mixture was reacted at room temperature for 10-12 hours. After dialysis and drying, chitosan-sorbic acid graft copolymer was obtained. Chitosan-sorbic acid graft copolymer and ethanol were mixed evenly, and sodium hydroxide solution was added to adjust the pH to 9-10. 2,3-epoxypropyltrimethylammonium chloride was added, and the mixture was reacted at 60-70℃ for 5-7 hours. After precipitation, filtration, washing, and drying, modified chitosan was obtained.

2. The processing technology of the anti-mildew and antibacterial polyolefin material according to claim 1, characterized in that: In step three, the mass ratio of vinyl nano zinc oxide, methyl methacrylate, double-bonded guanidine compound and modified chitosan is 1:(1-2):(2-4):(0.5-1.5).

3. The processing technology of the anti-mildew and antibacterial polyolefin material according to claim 1, characterized in that: The elastomer is one or more of the following: ethylene-hexene copolymer, ethylene-butene copolymer, and ethylene-octene copolymer.

4. The processing technology of the anti-mildew and antibacterial polyolefin material according to claim 1, characterized in that: The lubricant is one or a mixture of polypropylene wax, polyethylene wax, silicone masterbatch, polytetrafluoroethylene, and paraffin powder.

5. A mildew-resistant and antibacterial polyolefin material prepared by the processing technology according to any one of claims 1-4.

6. The application of the anti-mildew and antibacterial polyolefin material according to claim 5 in a toothbrush handle.

Citation Information

Patent Citations

  • Chitosan hydrogel for antibacterial dressing and preparation method thereof

    CN103920180A

  • Compound active peptide facial cleanser and preparation method thereof

    CN113425618A

  • Mould-proof and antibacterial agent for cloth processing and preparation method thereof

    CN113430827A

  • High-antibacterial polypropylene composite material and preparation method thereof

    CN117186539A